ASSISTANCE FOR THE COMMUNITY OF SEMPU HAMLET, NGADIROJO VILLAGE, MAGELANG REGENCY IN BIOCONVERSION OF ORGANIC WASTE INTO ALTERNATIVE FEED FOR MAGELANG DUCKS - Puji Rahayu, Tri; Trisnowati, Eli; Bayuaji Pramono, Pradipta (LPPM Univ. Ibn Khaldun Bogor, 2022)
Livestock is one of the livelihoods that contribute to the economy of the Indonesian people, one of which is the Magelang Duck livestock group